Performance analysis of PV/T modules with and without glass cover and effect of mass flow rate on electricity and hot water generation - Attakorn Asanakham; Thoranis Deethayat (Energy Reports, 2020)
Two types of hybrid photovoltaic/thermal (PV/T) modules, with and without glass cover for generating hot water and electricity (combined heat and power, CHP) were tested to investigate power generation performance in terms of generated power (Pe) with module temperature (Tm) and solar radiation level (IT); and thermal performance in terms of thermal efficiency (ηm) with(Tfi-Ta)/IT. A method for calculating the hot water temperature and the generated power was also developed and the results agreed well with the experimental data. With the model, the effect of water mass flow rate on the energy outputs was carried out by exergy analysis. It could be found that low second law efficiency was found with higher mass flow rate at low solar radiation level and high inlet water temperature.
Keywords: 330; Combined heat and power; Exergy; Performance analysis; Photovoltaic/thermal module; Water flow rate